Male gonadal function in coeliac disease: 2. Sex hormones. Issue 2 (February 1983) - Farthing, M J; Rees, L H; Edwards, C R; Dawson, A M
Abstract : Hypogonadism, infertility, and sexual dysfunction occur in some men with coeliac disease. We have measured plasma testosterone, dihydrotestosterone, sex-hormone binding globulin, oestradiol, and serum luteinising hormone in 41 men with coeliac disease and have related these findings to jejunal morphology, fertility, semen quality, and sexual function. To determine the specificity of these observations in coeliacs we also studied 19 nutritionally-matched men with Crohn's disease, and men with chronic ill-health due to rheumatoid arthritis and Hodgkin's disease. The most striking endocrine findings in untreated coeliacs were increased plasma testosterone and free testosterone index, reduced dihydrotestosterone (testosterone's potent peripheral metabolite), and raised serum luteinising hormone, a pattern of abnormalities indicative of androgen resistance. As jejunal morphology improved hormone levels appeared to return to normal. This specific combination of abnormalities was not present in any of the disease control groups and, to our knowledge, androgen resistance has not been described previously in any other non-endocrine disorder. Plasma oestradiol concentration was modestly raised in 10% of coeliacs and 11% of patients with Crohn's disease. Unlike plasma androgens and serum luteinising hormone in coeliacs, plasma oestradiol was not clearly related to jejunal morphology. Androgen resistance and associated hypothalamic-pituitary dysfunction appear to be relatively specific to coeliac disease and cannot be explained merely in terms of malnutrition or chronic ill-health. In addition, our findings suggest that this endocrine disturbance may be related to sexual dysfunction in coeliac disease but its relationship to disordered spermatogenesis in this condition has not been clearly established.